Cerebral vasculitis: imaging signs revisited. - Küker, W (2007)
Inflammatory stenoses of cerebral blood vessels, although rare in general, are an important cause of cerebral ischemia in younger patients. The diagnosis is often difficult. The first step in the diagnostic process is the identification of brain lesions consistent with cerebral vasculitis. Brain lesions are frequently found in this patient group, especially if modern imaging tools such as diffusion and perfusion-weighted imaging are employed. Although no specific pattern for this entity exists, multiple infarcts of various ages in more than one vascular territory should raise this suspicion. The next step in the imaging of patients with suspected vasculitis is the demonstration of the underlying vascular pathology. MR angiography is the mainstay of investigating patients for intracranial vascular stenoses. However, at 1.5 T it is only diagnostic for stenoses of large brain arteries. Hence, conventional angiography is still required to investigate stenoses of medium and small-sized brain arteries. Recent work suggests that MRI can directly demonstrate mural thickening and contrast enhancement in basal brain arteries, rendering biopsy obsolete in this patient group. A classification for cerebral vasculitis is proposed according to the size of the affected brain vessels, analogous to the pertinent nomenclature of primary systemic vasculitis.